2006
DOI: 10.1203/01.pdr.0000233252.60457.cf
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Neonatal-Onset Mitochondrial Respiratory Chain Disease with T Cell Immunodeficiency

Abstract: ABSTRACT:We present the clinical and laboratory features of a boy with a new syndrome of mitochondrial depletion syndrome and T cell immunodeficiency. The child suffered from severe recurrent infectious diseases, anemia, and thrombocytopenia. Clinically, he presented with severe psychomotor retardation, axial hypotonia, and a disturbed pain perception leading to debilitating biting of the thumb, lower lip, and tongue. Brain imaging showed hypoplasia of corpus callosum and an impaired myelinization of the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…None of the other mitochondrial patients had levels below cut-off in the neonatal screening sample. Included were patients with a POLG mutation, as well as Pearson syndrome, for which neutropenia and bone marrow failure have been reported [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…None of the other mitochondrial patients had levels below cut-off in the neonatal screening sample. Included were patients with a POLG mutation, as well as Pearson syndrome, for which neutropenia and bone marrow failure have been reported [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, severe T-cell immunodeficiency phenotypes have been described. Reichenbach et al (2006) reported a case of fatal neonatal-onset respiratory chain disease with T-cell immunodeficiency. The child suffered from severe recurrent infections, anemia and thrombocytopenia as well as defects in myelinization and brain development.…”
Section: Mitochondrial Disordersmentioning
confidence: 99%
“…He was heterozygous for the p.Arg1187Trp mutation, previously identified in a patient with mitochondrial depletion syndrome and T-cell immunodeficiency. 17 However, the involvement of this mutation in the patient's disease is not obvious given that the pathogenesis of this mutation is still unclear and the parents are consanguineous.…”
Section: Resultsmentioning
confidence: 99%